2015
DOI: 10.4269/ajtmh.14-0554
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HIV Progression During Acute HIV-1 Subtype C Infection in a Mozambican Patient with Atypical Seroconversion

Abstract: Abstract. Acute human immunodeficiency virus (HIV) infection (AHI) refers to the period between viral transmission and development of an adaptive immune response to HIV antigens (seroconversion) usually lasting 6-8 weeks. Rare cases have been described in which HIV-infected patients fail to seroconvert and instead, develop rapid HIV-mediated clinical decline. We report the case of a Mozambican woman with AHI and malaria coinfection who showed atypical seroconversion and experienced rapid deterioration and deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Virological factors that impair the in vivo viral fitness have also been shown to contribute to this phenotype 5 . In an opposed setting, high levels of viral replication, either as a consequence of poor or inefficient immunological responses or particular viral cytopathic factors, are associated with rapid progression to AIDS 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Virological factors that impair the in vivo viral fitness have also been shown to contribute to this phenotype 5 . In an opposed setting, high levels of viral replication, either as a consequence of poor or inefficient immunological responses or particular viral cytopathic factors, are associated with rapid progression to AIDS 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that circulating virus in Mozambique is almost exclusively HIV-1 Group M subtype C ( Engelbrecht et al., 1998 ; Bellocchi et al., 2005 ; Parreira et al., 2006 ). One acute HIV case was the subject of a published case report ( Velasco et al., 2015 ) and had sequencing completed to confirm subtype C.…”
Section: Methodsmentioning
confidence: 99%